2009
DOI: 10.4076/1757-1626-2-6787
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from a case of osteopetrosis oxycephaly and Chiari type I malformation: a case report

Abstract: We report a child with osteopetrosis, oxycephaly and Chiari type I malformation who presented with raised intracranial pressure. During cranial expansion surgery the patient developed sudden cardiac arrest which we believe was probably related to the Chiari malformation. The case highlights a previously unrecognized association between osteopetrosis, craniosynostosis and a persistently open fontanelle at age 4 years. In addition it supports the existing literature in emphasizing the need for careful preoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…[22] Searching the literature indicated that the combination of the three abnormalities together (OP, CM1, and CS) was mentioned only once, with no mentioned genetic studies. [4]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] Searching the literature indicated that the combination of the three abnormalities together (OP, CM1, and CS) was mentioned only once, with no mentioned genetic studies. [4]…”
Section: Discussionmentioning
confidence: 99%
“…[13] The triad of the three abnormalities has been published only once, however, with no genetic study. [4] Herein, we describe another patient with malignant OP, CS, and CM1. Molecular testing revealed novel mutation homozygous in OSTEM1 gene.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, there are 5 pediatric cases of autosomal recessive osteopetrosis associated with hindbrain herniation (Table 1). 3,17,18 The causative role of osteopetrosis with CM-I is unclear. Hypotheses include mass effect from the significant calvarial thickening and subsequent downward tonsillar herniation.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in cranial capacity related to thickening of the calvaria is thought to contribute to elevated ICP in these cases, 2,4,6,20,39 and narrowing of the cranial nerve foramina has led to deafness, facial paresis, blindness, and sequelae of brainstem compression. 2,5,9,12,20,25,32,35,63 Pediatric neurosurgical intervention in these rare cases has been described since the late 1960s, when Baird et al first described VP shunting for a 3-month-old boy with osteopetrosis and hydrocephalus. 15,37,51 Variable degrees of posterior fossa crowding and CTH in osteopetrosis are also frequently mentioned in available literature and appear to be common findings in these rare cases, with the majority of cases associated with concomitant triventricular hydrocephalus.…”
Section: Involvement Of Pediatric Neurosurgerymentioning
confidence: 99%
“…15,37,51 Variable degrees of posterior fossa crowding and CTH in osteopetrosis are also frequently mentioned in available literature and appear to be common findings in these rare cases, with the majority of cases associated with concomitant triventricular hydrocephalus. 2,5,9,12,20,25,32,35,63 Increased ICP In osteopetrosis, the decrease in cranial capacity resulting from thickening of the calvaria contributes to the elevated ICP seen in these cases. 6 While mostly outside of the United States, several reports have surfaced since that time, describing children with this disease coming to neurosurgical attention.…”
Section: Involvement Of Pediatric Neurosurgerymentioning
confidence: 99%